Leadership trends and challenges in school-based management: A case study of Calubian North District, Leyte, Philippines - Niez, Roland; Tancinco, Noel; Retuerto, Genie; Vicera, Christopher; Ang, Jason (International Journal of Innovative Research and Scientific Studies, 2025)
This study aimed to investigate the trends and challenges faced by school leaders in the Calubian North District, Calubian, Leyte, focusing on School-Based Management (SBM). Employing a mixed-methods research design, 11 school leaders participated in a survey questionnaire and interviews to achieve the study's objectives. Findings indicate that most school leaders in the Calubian North District are female, married, and in the prime working age. The majority hold doctorate degrees, serve as Principal II, have less than ten years of administrative experience, and have attended national training. Schools 9 and 14 exhibit larger teacher and student populations compared to others in the district. Regarding SBM levels, most schools in the district are classified as Level 1. Trends among school leaders include fostering trust among staff, students, parents, and community partners, effectively managing fiscal, human, and material resources, and enhancing curriculum and instructional resources. Challenges identified through interviews include physical facilities/resources, human resources management, community engagement, and instructional issues. Significant findings show that administrative experience influences SBM levels, while trends among school leaders correlate significantly with SBM effectiveness. In conclusion, the study highlights the proactive engagement of school leaders in fostering stakeholder partnerships. Recommendations include conducting assessments of challenges faced by school leaders and implementing targeted interventions through division program supervisors within the Department of Education.